Sticky behavior of R&D costs and its relevance to firm value: Evidence from listed companies in Korea - Moon Hyun Kym (Global Business & Finance Review (GBFR), 2023)
Purpose: The purpose of this study is to investigate the impact of sticky behavior in R&D costs on firm value. The study aims to gain insights into whether the stickiness of R&D costs is a rational choice based on managerial foresight or if it stems from managerial self-interest. Design/methodology/approach: For the regression analysis, a modified version of Ohlson's accounting-based valuation model (1995) was used to assess the impact of R&D costs on firm value. and the stickiness of R&D costs was measured using the model proposed by Homburg & Nasev (2009). International Financial Reporting Standards were adopted in Korea in 2011, and empirical analysis was subsequently conducted using data from listed companies. Findings: The empirical results were as follows. Firstly, R&D costs reported as expenses showed a negative (-) correlation with firm value, while the stickiness of R&D costs was found to have a positive (+) impact on the value relevance of earnings. Secondly, R&D costs reported as assets did not have a significant impact on firm value, and the stickiness of R&D costs did not have a significant impact on the value relevance of net assets. Research limitations/implications: Overall, the findings of this study support the accounting treatment of R&D costs as expenses. Moreover, the study reveals that the sticky behavior of R&D costs helps alleviate the negative value relevance of R&D expenses. Originality/value: This study distinguished between capitalized R&D costs and expensed R&D costs, and examined their value relevance by investigating the impact of sticky behavior on earnings and net assets.
Keywords: 650; Expensed R&D costs; Capitalized R&D costs; Sticky Cost Behavior; Value Relevance